Safety first: Beliefs of older peers supplying alcohol to underage friends. (28th August 2020) - Lam, Tina; Fischer, Jane; Salom, Caroline; Ogeil, Rowan; Wilson, James; Lubman, Dan I.; Burns, Lucinda; Lenton, Simon; Gilmore, William; Chikritzhs, Tanya; Aiken, Alexandra; Allsop, Steve
Abstract: Issue addressed: Underage drinkers most commonly source alcohol from older peers. However, few studies have examined older peers' supply‐related beliefs and motivations. Methods: A sample of 270 risky drinkers aged 18‐19 years were interviewed in Australia where the legal purchase age is 18. They were asked about their provision to underage friends, awareness of secondary supply legislation (intended to prohibit such supply) and 24 psycho‐legal beliefs around supply. Results: Half (49%) provided alcohol to a 16‐ to 17‐year‐old friend to drink at a party they were both attending at least twice a year. Three‐quarters reported provision was okay so long as the recipient(s) were in a safe environment, and 46% reported "everyone gives alcohol to teenagers if they are in a safe environment." There was significantly higher agreement that "my friends would think I was mean if I did not give alcohol to a friend under the age of 18" (37%), compared to "my friends would think I was uncool if I did not give alcohol to a friend under the age of 18" (26%). Two thirds (69%) felt more responsible for an underage friend's safety if they provided the alcohol. A multivariate logistic regression revealed supply was more likely if the supplier: was aged 18 compared to 19 (95% CI OR: 1.57, 4.84), male (1.06, 3.27), of a higher SES quintile (1.08, 1.80) and believed alcohol supply to minors was morally acceptable (1.01, 1.33) and normal (1.04, 1.38). Knowledge of regulatory strategies (68%) designed to prevent supply to minors, and their perceived deterrent value did not significantly impact supply. Conclusions: Supply of alcohol to underage peers was perceived as morally and socially acceptable in a group of 18‐ to 19‐year‐old risky drinkers. So what?: Opportunities include harm reduction initiatives that prioritise caring responsibilities towards friends, as opposed to relying on external enforcement measures alone.